(untitled) (Annals of Medical Research, 2022)
Aim: It is aimed to evaluate the effect of reflux time in primary VUR in terms of predicting endoscopic treatment success and treatment timing in VUR management. Vesicoureteral reflux (VUR) is an important cause of urinary tract infection and chronic renal disease. Voiding cystourethrography (VCUG) is the gold standard diagnostic test in the diagnosis of VUR. In recent years, new parameters related to VCUG have been more objectively studied to evaluate the clinical prognosis. Materials and Methods: In our study, the records and imaging findings of children with primary VUR who underwent VCUG examination between 2012 and 2019, who were treated with endoscopic injections, were retrospectively reviewed. Forty-one children (67 renal units) were included in our study. Patients with preoperative VCUG, urinary ultrasonography, dimercaptosuccinic acid (DMSA) renal scan, and post-operative control VCUG were included in this study. Results: Patients with preoperative VUR grade 1-2 were divided into two groups as “low grade” and patients with stage 3-4-5 as “high grade”. In the general patient population, endoscopic success rates in terms of renal unit deficit were found to be 46.3% (31/67). When the subgroup was analyzed, the endoscopic treatment success rate was 72.2% (13/18) in the low-grade group, versus 36.7% (18/49) in the high-grade group (p = 0.010). In the multivariate logistic regression analysis performed to identify independent predictors of scarring, reflux degree and reflux time were found to be independent predictors of scarring. Conclusion: In our study, we found that in VCUG evaluated preoperatively, VUR time as well as VUR grade were effective on endoscopic success rate and scar development. Based on these results, it could be thought that VUR time may be effective in selecting the best candidates for surgery and in the management and timing of treatment of VUR patients.